The pessimist's guide to history : an irresistible compendium of catastrophes, barbarities, massacres, and mayhem - from 14 billion years ago to 2007 /: an irresistible compendium of catastrophes, barbarities, massacres, and mayhem - from 14 billion years ago to 2007. ([2009?]) - Unknown
No abstract available